Model based PEM fuel cell state-of-health monitoring via ac impedance measurements - Fouquet, N.; Doulet, C.; Nouillant, C.; Dauphin-Tanguy; Ould-Bouamamab, B.
The present paper deals with monitoring of flooding and drying out of a proton exchange membrane (PEM)fuel cell using a model-based approach coupled with ac impedance measurements. A study of the impedance response of a 150 cm2 six-cell air/H2 PEM fuel cell as a function of inlet gas relative humidity was carried out. Parameters of a Randles-like equivalent circuit were then fitted to the data. In order to improve the quality of the fit, the classical Randles cell was extended by changing the standard plane capacitor into a constant phase element (CPE). It was found that monitoring the evolution of the three resistances of this modified Randles model was an efficient and robust way of monitoring the state-of-health (SOH)of the fuel cell with respect to the water content of the membrane electrode assembly. Moreover, the non-integer power of the CPE was found to be statistically constant over a wide range of operating conditions, thus comforting the assumption that it has a physical meaning. Qualitative interpretation of the ariation of the parameters as a function of the SOH is proposed in both flooded and dry conditions.
Keywords: PEM FUEL CELL; WATER MANAGEMENT; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; MODEL-BASED FAULT DETECTION AND ISOLATION